Investigation of the Techno-Economical Feasibility of the Power-to-Methane Process Based on Molten Carbonate Electrolyzer - Monzer, Dayan; Rivera-Tinoco, Rodrigo; Bouallou, Chakib (Frontiers in Energy Research, 2021)
High-temperature steam/CO2 electrolysis process has been the scope of study for the last decades. This study confers a feasible and environmental approach to convert low-carbon electrical energy into chemical energy, stored in the form of synthetic gas (H2 and CO) to be further processed in line with the final use target. It focuses on the Power-to-Methane technology using a high-temperature molten carbonates electrolyzer (MCEC). A large-scale process composed of the built-in MCEC model and the Balance of Plant (BOP) equipment is proposed and simulated with AspenPLUS software, taking into consideration the possible heat integration in the system for saving energy consumption. The proposed full-based process system shows an overall efficiency of 72%. The employment of this carbon neutral process relies on its economic competitiveness. For this reason, an economic assessment is conducted to investigate the economic feasibility of the proposed process. Indeed, the current methane production cost resulting from this process is not as competitive as market prices induced by other technologies. However, a parametric study demonstrating the impact factors on the methane selling price reveals that amelioration in the lifespan of the electrolyzer, accompanied by a reduction in its cost, can be an attractive solution, given the current market technology. This overall analysis sheds light on the role of the proposed process as an environmental-friendly and cost feasible solution for synthetic methane production.